The woman's wakeup : how to shake up your looks, life, and love after 50 - Johnson, Lois Joy (Running Press, 2015)
"The Woman's Wakeup is a user-friendly, inspirational guide that provides firsthand advice for women on everything from dating (again!) to being a glam grandmother, reviving a wardrobe, making friends in a new town, working in a new environment, and figuring out how to stand out in a youth-obsessed world. Filled with Johnson's expert tips--as well as interviews with medical professionals and women 50+ of various walks of life who have been there, done that, and are still on the road to adventure--The Woman's Wakeup will inspire you to feel more confident, stylish, and evolved than ever,"--Amazon.com.